(untitled) - Rodriguez-Saona, Roberto (London, 2004)
Colloquial Spanish of Latin America 2 is designed to help those involved in self-study. Structured to give you the opportunity to listen to and read lots of modern, everyday Latin American Spanish, it has been developed to work systematically on reinforcing and extending your grasp of the grammar and vocabulary.
Keywords: Spanish language,Spanish language,Spanish language,Spanish language; Conversation and phrase books,English,Textbooks for foreign speakers,English,Dialects,Latin america,Spoken spanish,Latin america